Problem Solving Ability in Mathematics Among Secondary School Students: A study - Azam HUSSAIN; Viquar UNNISA; Mousuf RAZA (International Journal of Environmental, Sustainability, and Social Science, 2025)
This study explores the problem-solving capability in mathematics among secondary school students. The aim of the study was to find out the problem-solving capability in mathematics among students based on schools, level, and gender. Descriptive survey method was used in this study. Secondary schools of the Samastipur district were included as the population, and one hundred students of class IX from two Government and two private schools of Shahpur Patory were selected as the sample, and convenience sample was adopted in the sampling technique. Mean, percentage, SD and t-test were used as the statistics in this study. Data obtained from secondary school students were analysed using SPSS. The results indicates that the level of problem-solving capability in mathematics among secondary school students was 25% low level. 54% of the students were average level, while 21% of the students were high level. Conclusion revels that there is no significant difference between males and females in solving problems in mathematics among secondary school students and no significant difference in solving problems in mathematics between students in private schools and public schools.